P487 A novel rapid real-time PCR test for the detection of Chlamydia trachomatis in patient samples. (14th July 2019) - Cornwell, Clare; Scully, Philip; Tyson, John; Sails, Andy; Ohalloran, Jonathan
Abstract : Background: Point of care (POC) testing for infectious diseases can provide actionable diagnostic information as soon as individuals present to healthcare systems. POC testing for sexually transmitted infections could have a significant impact on sexual health by enabling screening programs, reducing loss to follow-up and enabling immediate and targeted treatment. We have developed a novel rapid real-time PCR assay which can detect Chlamydia trachomatis in clinical samples. Methods: DNA was extracted from 122 residual genital swab and urine samples previously tested in the Roche cobas CT/NG assay using the Qiagen DNA mini kit and the DNA extracts were tested for C. trachomatis using the rapid real-time PCR assay. Results: Of the 122 samples, forty were negative in both the new rapid real-time PCR assay and the Roche cobas assay; 78 samples were positive in both assays and four samples were positive in the cobas assay but negative in the new novel assay. The specificity of the new novel assay was 100% and its sensitivity was 95.1% respectively. The four samples which were negative in the new assay had high Ct values in the cobas test indicating low levels of chlamydia organisms were present in the samples. Conclusion: The rapid real-time PCR system is rapid, sensitive and specific for the detection of C. trachomatis in clinical samples from patients with chlamydia infection. The rapid real-time PCR assay for C. trachomatis forms the basis for a low cost, disposable sample to answer diagnostic assay cassette, which will run on the QuantuMDx Q-POC™ platform. Disclosure: No significant relationships.